Disseminated Balamuthia mandrillaris Infection - Schafer, Katherine R. (J Clin Microbiol, 2015)
Balamuthia mandrillaris is a rare cause of human infection, but when infections do occur, they result in high rates of morbidity and mortality. A case of disseminated Balamuthia infection is presented. Early diagnosis and initiation of recommended therapy are essential for increased chances of successful outcomes.